DEVELOPING INDUCTIVE THINKING KIT TO IMPROVE REPRESENTATION DATA AND SCIENTIFIC REASONING SKILLS - Yudi Guntara; Insih Wilujeng (Universitas Negeri Yogyakarta, 2018)
This study was aimed at producing and examining the effectiveness of physics learning kit of inductive thinking model which is reasonably to increase students’ data representations and scientific reasoning skills. This research uses RD methods with 4D models that consists of define (need analysis of learning), design (designing the product draft), develop (expert appraisal, product field testing, and product revising), and disseminate (disseminating final product). The physics learning kit of inductive thinking model which is developed consists of syllabus, lesson plan, handout, worksheet and skills assessment sheet. The data were analyzed using the descriptive statistics, N-Gain analysis, multivariate test statistic Hotelling’s T2 and effect size analysis. The result of this research produced the physics learning kits of inductive thinking model which is reasonably used to increase students’ data representations and scientific reasoning skills with very good category based on experts, teachers and response of students. The learning kit is effective to increase students’ data representations and scientific reasoning skills significantly by effect size analysis with f = 0.180 for data representations skills and f = 0.115 for scientific reasoning skills.PENGEMBANGAN PERANGKAT INDUCTIVE THINKING UNTUK PENINGKATAN KEMAMPUAN REPRESENTASI DATA DAN PENALARAN ILMIAHAbstrakPenelitian ini bertujuan untuk menghasilkan dan menguji efektivitas perangkat pembelajaran fisika model inductive thinking yang layak dalam meningkatkan kemampuan representasi data dan penalaran ilmiah siswa SMA. Penelitian menggunakan metode RD dengan model 4D yang meliputi tahap define (analisis kebutuhan pembelajaran), design (perancangan draf produk), develop (penilaian ahli dan guru, uji coba produk, revisi produk), dan disseminate (penyebarluasan produk akhir). Produk perangkat pembelajaran fisika model inductive thinking yang dikembangkan ini terdiri dari silabus, RPP, handout, LKS dan lembar penilaian kemampuan. Teknik analisis data menggunakan statistik deskriptif, analisis N-Gain, uji statistik multivariat Hotelling’s T2 dan analisis effect size. Hasil penelitian menunjukkan bahwa perangkat pembelajaran fisika model inductive thinking layak digunakan dalam pembelajaran dengan kategori sangat baik berdasarkan penilaian ahli, guru, dan respons siswa. Perangkat yang dikembangkan efektif dalam meningkatkan kemampuan representasi data dan penalaran ilmiah berdasarkan analisis effect size dengan nilai f=0,180 terhadap kemampuan representasi data dan f=0,115 terhadap kemampuan penalaran ilmiah.